Analisis Pengaruh Jumlah Industri Besar Dan Upah Minimum Provinsi Terhadap Pertumbuhan Ekonomi Di Provinsi Aceh - Meurah Intan; Yoyon Safrianto (Universitas Teuku Umar, 2022)
The number of large industries actually really helped of public and governments in terms of revenue or income where by the presence of large industries so minimum wage workers can be set in accordance with the need. Wages is a concrete manifestation of a form of an exchange that occurs between users of services and providers, minimum wages to into a minimum standards used by the entrepreneurs or to the offender industry for provides wages to workers in effort or it works .This research used a regression spss version 17. Based on the results of research conducted, so it can be concluded is as follows: linear regression equation the results and the worship of idols can be seen that the value of X1 (the number of large industries) as much as -0,055X1 meaning that the number of large industries aceh province are reduced as much as 1 unit and would cause a decrease of percent 0,055. T acount value on the variable of X1 (big industries) greater than the ttable (2,302>1,796), significance to the level of errors α = 0,050 ( 0,042<0,050 ), which means that the number of big industries a factor that can promote economic growth significantly. Based on the result of multiple linear regression can be seen that the UMP of -3,839 means when down by the UMP 1 will cause a decrease in economic growth at -3,839 percent. UMP less than of the ttable (1,107<1,796 ), lt significance to the level of errors α = 0,050 ( 0,292>0,050 ), this means the ump was the factor that cannot increase economic growth significantlyKeywords: economic growth, provincial minimum wage, the number of industry